Day 1 Wed, April 05, 2017 2017
DOI: 10.2118/185889-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Drilling Fluid Invasion, Clean-Up, and Retention During Reservoir Formation Drilling and Completion

Abstract: A reservoir-conditions coreflood study was undertaken to assist with design of drilling and completion fluids for a Norwegian field. Multiple fluids were tested, and the lowest permeability alterations did not correlate with the lowest drilling fluid filtrate loss volumes. This paper will examine the factors which contributed to alterations in the core samples. A series of corefloods were carried out using core from 2 formations and different drilling fluids. Separate tests were carried out usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…When conducting core flood studies to assist in designing of drilling and completion fluids in 2017, Green et al [16] found that the lowest permeability alterations did not correlate with the lowest drilling fluid filtrate loss volumes. They concluded that the major formation damage is more likely to be caused by the drilling fluid filter cake's ability to stick to the formation and whether it can be removed during production.…”
Section: Introductionmentioning
confidence: 99%
“…When conducting core flood studies to assist in designing of drilling and completion fluids in 2017, Green et al [16] found that the lowest permeability alterations did not correlate with the lowest drilling fluid filtrate loss volumes. They concluded that the major formation damage is more likely to be caused by the drilling fluid filter cake's ability to stick to the formation and whether it can be removed during production.…”
Section: Introductionmentioning
confidence: 99%